2005
DOI: 10.1021/es0493648
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics and Modeling of the Fe(III)/H2O2 System in the Presence of Sulfate in Acidic Aqueous Solutions

Abstract: This work examined the effect of sulfate ions on the rate of decomposition of H2O2 by Fe(III) in homogeneous aqueous solutions. Experiments were carried out at 25 degrees C, pH < or = 3 and the concentrations of sulfate ranged from 0 to 200 mM ([Fe(III)]0 = 0.2 or 1 mM, [H2O2]0 = 10 or 50 mM). The spectrophometric study shows that addition of sulfate decreased the formation of iron(III)-peroxo complexes and that H2O2 does not form complexes with iron(III)-sulfato complexes. The rates of decomposition of H2O2 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
81
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 148 publications
(83 citation statements)
references
References 45 publications
1
81
0
1
Order By: Relevance
“…classical Fenton process [9][10][11][12][13][14][15][16], Fenton-like treatment [17][18][19] and photo-Fenton process [20][21][22]. However, only two papers refer to electro-Fenton process [23,24].…”
Section: Ar(hoh) • + O 2 → Ar(oh) + Homentioning
confidence: 99%
See 1 more Smart Citation
“…classical Fenton process [9][10][11][12][13][14][15][16], Fenton-like treatment [17][18][19] and photo-Fenton process [20][21][22]. However, only two papers refer to electro-Fenton process [23,24].…”
Section: Ar(hoh) • + O 2 → Ar(oh) + Homentioning
confidence: 99%
“…The hydroperoxo iron complexes that could be formed [17] would not reduce the availability of iron since they can regenerate Fe 2+ from Eqs. 4a to 4c [5],…”
Section: -mentioning
confidence: 99%
“…Sulfate ion is often present in photo-Fenton reactions as a result of the addition of iron in the form of readily available sulfate salts (De Laat & Le, 2005). Sulfate ion complexes strongly with Fe(III) over a wide pH range ( Figure 7) and the quantum yield of production of Fe 2+ plus a sulfate anion radical from photolysis of Fe(SO 4 ) + is only about 0.05 (Benkelberg & Warneck, 1995).…”
Section: Inhibition Of the Photo-fenton Reaction By Sulfate Ionmentioning
confidence: 99%
“…A more detailed summary and description of Fe III -induced Cl 2 formation can be found in Lim et al [24] or Wittmer et al [15] In addition to the photosensitive iron-induced halogen release mechanism, further trace gas species, such as O 3 , NO x and sulfur dioxide (SO 2 ), possibly influence Cl 2 release, mainly when dissolved in the aqueous phase where they can change the pH, [25] coordinate with Fe 2þ or Fe 3þ , [26] scavenge Cl [22] or additionally activate halides by the known heterogeneous mechanisms. [13] Concerning O 3 , Sadanaga et al [27] observed an enhancement of the O 3 uptake rate and Cl 2 release in the presence of water-soluble Fe 3þ and O 3 in the dark.…”
Section: Introductionmentioning
confidence: 99%